2019
DOI: 10.1515/hf-2018-0236
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pits in parenchyma cells of the moso bamboo [Phyllostachys edulis (Carr.) J. Houz.] culm

Abstract: The pits on parenchyma cell walls facilitate transfer of liquids between adjacent cells in the bamboo. To better understand the structure-function relationship of the pits, the structural characteristics of the pits in bamboo parenchyma cells need to be investigated. In this study, the pit structures were studied by field-emission environmental scanning electron microscopy (SEM). The samples included the native structure and the replica structure via resin castings. The results showed that the parenchyma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 18 publications
4
2
0
Order By: Relevance
“…In this study, we found that the pit was mainly in simple pit pair, with the pit pairs of adjacent cells connected by plasmodesmata at the primary cell wall, which is consistent with the type of pits and the way they are connected in the cell walls of plants such as Wheat, Eucommia and Mao bamboo ( Kristensen et al., 2008 ; Fromm, 2013 ; Lian et al., 2019 ). By analyzing the direction of transport of highly electron-dense material within the pits, it was hypothesized that the role of the pits on pear stone cells was to transport degraded material out of the cell from PCs which were beginning to lignify, and that the transported materials might contain some kind of signalling molecules that could initiate the process of lignification in PCs, thus accelerating the process of lignification in PCs surrounding the stone cells.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, we found that the pit was mainly in simple pit pair, with the pit pairs of adjacent cells connected by plasmodesmata at the primary cell wall, which is consistent with the type of pits and the way they are connected in the cell walls of plants such as Wheat, Eucommia and Mao bamboo ( Kristensen et al., 2008 ; Fromm, 2013 ; Lian et al., 2019 ). By analyzing the direction of transport of highly electron-dense material within the pits, it was hypothesized that the role of the pits on pear stone cells was to transport degraded material out of the cell from PCs which were beginning to lignify, and that the transported materials might contain some kind of signalling molecules that could initiate the process of lignification in PCs, thus accelerating the process of lignification in PCs surrounding the stone cells.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we found that the pit was mainly in simple pit pair, with the pit pairs of adjacent cells connected by plasmodesmata at the primary cell wall, which is consistent with the type of pits and the way they are connected in the cell walls of plants such as Wheat, Eucommia and Mao bamboo (Kristensen et al, 2008;Fromm, 2013;Lian et al, 2019). By analyzing the direction of transport of highly The width of Secondary wall layer of DY and DW.…”
Section: Discussionsupporting
confidence: 77%
“…The porosity of the scaffold increased from 31 ± 4 to 86 ± 3% (eq 1 and Figure S1). The pore size distribution results (Figure C and Table S1) showed that the hierarchical delignified bamboo includes vessels and sieve tubes having the largest conduit pores with a size of 50–120 μm diameter (20%), parenchyma cell lumen with a medium size of 10–50 μm (46%), and the smallest pores in teh inner cell wall with a size range of 0.5–10 μm (24%), which is consistent with reported results. The SEM images of raw bamboo and the delignified bamboo scaffold (Figure S2A,B) show that the micropores were exposed significantly after delignification. SEM analysis (Figures D­(1) and S2B,C) showed vast micropores in the range of 15–120 μm with a hairy fracture surface.…”
Section: Results and Discussionsupporting
confidence: 89%
“…The results of the free enzyme we obtained are comparable with the published data. ,, Generally, the biocatalytic processes involve both molecular and convective diffusion including substrate diffusion to catalytic sites and product diffusion back to the solution. , Moreover, the density of BGU immobilized at different locations of the hierarchical scaffold should be different due to the gradient distribution of the vascular bundles from the inner skin to the outer skin . In our system, molecular diffusion could be affected by the bamboo structure including their internal geometry. The rates of adsorption and desorption of small molecules (both the substrate and the product) by bamboo are related to the external diffusion coefficient and the internal resistance (due to the boundary layer, the diffusion in the materials, etc. ). , Under some conditions, the apparent diffusion coefficient could be positively correlated with the materials’ thickness .…”
Section: Results and Discussionsupporting
confidence: 83%
“…[ 24 ] The micropores on the pit membrane range in size from around 2–50 nm to more than 50 nm. [ 25 ] The equivalent pore size spanned between 10 and 100,000 nm in Figure 4B, and the range was influenced by density fluctuations in the curve between 10–100 and 5000–90,000 nm. The pore size range of 10–100 nm was primarily consistent with the pit of bamboo.…”
Section: Resultsmentioning
confidence: 99%